(untitled) (Canadian Dermatology Today, 2023)
Skin resurfacing refers to the therapeutic act of delivering a controlled injury to the skin to improve surface characteristics such as pigment, texture and rhytides. Consequently, many dermatology patients may benefit from resurfacing, whether they have actinic damage, solar lentigines, acne scarring or elastosis. Although there are many resurfacing modalities beyond lasers (i.e., microneedling, chemical peels, mechanical dermabrasion, microneedling-radiofrequency, etc.), this article will primarily address fractional laser resurfacing. Reviewing fully ablative laser resurfacing is beyond the scope of this article, although the use of fully ablative lasers for ablation of benign skin lesions will be discussed.